PELATIHAN DIGITAL MARKETING SEBAGAI STRATEGI BRANDING DI DESA WISATA SOEKA - Permadhi, Rissa Asyofa; Azhar, Wida Aulia; Ashsholihah, Zidnatuqo; Latifah, Fathya Nur; Azizah, Pepy Sophia Nur (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The existence of Soeka Tourist Village, which is relatively new in the tourism sector in Tasikmalaya Regency, requires the use of communication media as a marketing tool. The increasing use of technology and the internet has had a significant impact on various aspects of life, including the development of tourist villages. One effort to optimize technology use is to conduct digital marketing training aimed at enabling the residents of Sukaasih village to utilize social media for tourist village promotion as a digital marketing strategy for Soeka Tourist Village. The training involved 6 participants from Sukaasih village. Based on the pre-test and post-test questionnaires distributed to the participants, the pre-test percentage was 78%, and the post-test result was 51.67%, indicating a significant decrease in understanding and digital marketing strategy. Keywords: Digital Marketing, Training, Tourist Village